Penerapan Knowledge Capture Pada Aktivitas Pemantauan Hasil Audit Satuan Pengawasan Internal - Agus Prayitno (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The follow-up monitoring activity of the audit results is one of the activities carried out by the Internal Auditor after the publication of the Internal Audit Report. In minimizing delays in the completion of follow-up recommendations from the internal audit report, Knowledge Capture activities are needed to capture tacit knowledge in the activities of monitoring audit results by internal auditors. The knowledge capture techniques used by the authors in this study are interviews and on-site observation, as well as conceptual methods adopted from Alan Hevner's framework. This research aims to provide proposed improvement recommendations and find factors that cause delays in completing audit report recommendations so that, with the proposed improvements obtained from knowledge capture, the organization is able to minimize the impact of the risk of wasted time loss, additional costs, and stacked work for auditors. The proposed improvement is 1) the people aspect, organizations can hold knowledge sharing periodically and tiered according to the level of auditor competence and map the level of auditor competence, which is then used as a basis for training submissions for auditors. 2) As a process aspect, the organization will compile a follow-up monitoring procedure for audit report recommendations, which will then be socialized to Auditee in order to increase the level of understanding related to the completion of follow-up audit report recommendations.3) Furthermore, for the technological aspect, organizations should develop a web-based Follow-up Audit Report Recommendation Monitoring.